Experimental and Numerical Investigations in Materials Science and Engineering Proceedings of the International Conference of Experimental and Numerical Investigations and New Technologies, CNNTech 2018 - Mitrovic, Nenad; Milosevic, Milos; Mladenovic, Goran; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a collection of high-quality peer-reviewed research papers presented at the International Conference of Experimental and Numerical Investigations and New Technologies (CNNTech2018), held in Zlatibor, Serbia from 4 to 6 July 2018. The book discusses a wide variety of industrial, engineering and scientific applications of engineering techniques. Researchers from academia and the industry share their original work and exchange ideas, experiences, information, techniques, applications and innovations in the field of mechanical engineering, materials science, chemical and process engineering, experimental techniques, numerical methods and new technologies.
Keywords: Engineering mathematics; Engineering -- Data processing; Materials science; Mathematical and Computational Engineering Applications; Materials Science